BEGINNER TO USE FOREIGN EXPERIENCE IN PROVIDING INTERDISCIPLINARY CONNECTIVITY IN EDUCATION - Gulnora Narmatova Tojievna (Scholars Digest Publishing, 2023)
Interdisciplinary connectivity in education is the integration of knowledge, skills, and perspectives from various disciplines to address real-world problems. It encourages students to think critically, make connections, and approach challenges from multiple angles. Foreign experiences in education refer to successful strategies and practices adopted in other countries that promote interdisciplinary learning. This article explores the benefits and methods of incorporating foreign experiences into educational practices, presents results from selected case studies, discusses the implications, and offers conclusions and suggestions for implementation.
Keywords: Interdisciplinary connectivity, education, foreign experience, collaboration, methods, results, discussion, conclusions, suggestions.